Empfehlungen der AGERA zum Einsatz objektiver Hörprüfmethoden im Rahmen der pädaudiologischen Konfirmationsdiagnostik (Follow-up) nach nicht bestandenem Neugeborenen-Hörscreening - Hoth, Sebastian (HNO, 2012)
This paper presents the recommendations compiled by the German Electric Response Audiometry Working Group (Arbeitsgruppe Elektrische Reaktions-Audiometrie, AGERA) and the Association of German Audiologists and Neuro-otologists (Arbeitsgemeinschaft Deutschsprachiger Audiologen und Neurootologen, ADANO) for infants that fail newborn hearing screening (NHS) tests. Outlined are procedures for follow-up diagnosis using objective hearing tests to rule out or confirm a therapeutically relevant auditory defect and assessment of the severity thereof.